The URGENSI KETERANGAN AHLI HUKUM SEBAGAI ALAT BUKTI DALAM PENGUJIAN FORMIL UNDANG-UNDANG - Febry Indra Gunawan Sitorus, S.H. (Jurnal Hukum Lex Generalis, 2023)
This article aims to describe the position of legal expert's testimony in a formal constitutional review and what is the urgency. The result show that: first, the constitutional court recognizes the testimony of legal experts as one of the evidence as secondary evidence; second, in practice, there is no decision was found the constitutional judges elaborated the evidence of legal expert testimony in the verdict. Rrecommendation: First; to reconstruct the position of legal expert testimony in the formal constitutional review; Second; the Constitutional Court should firmly stipulate that the testimony of legal experts cannot be submitted as an evidence. Keywords: Formal Constitutional Review of Law, Evidence, Legal Expert Evidence